Adaptation and validation of the punitivism scale to the Argentine context - Roca, Marcelo Agustin (2025)
Punitivism can be defined as the collective preference for punitive measures and increased control over criminals. Understanding punitivism from a psychological perspective involves examining how individuals make decisions based on their beliefs, experiences, and emotions. The punitivism scale developed by Roberts et al. (2011) comprises seven items in a five-point Likert format, designed to assess individuals’ support for harsher punishments for criminal behavior. However, this construct has received limited attention in psychology, and no validated scale has yet been applied in the Argentine context. This study aims to adapt and validate the Roberts et al. punitivism scale for use in Argentina. A pilot study was conducted with a sample of 401 individuals, and an exploratory factor analysis was carried out. A subsequent final study involved a different sample of 458 participants, in which a confirmatory factor analysis was performed. One item showed inconsistencies and was therefore removed. The result was a unidimensional six-item scale with good model fit and acceptable reliability indices. This work contributes to the understanding of punitivism in the Argentine population and offers a reliable tool for future research on this topic in the local context.